The venomous course of southwestern opium: Qing prohibition in Yunnan, Sichuan, and Guizhou in the early nineteenth century - Bello, David (The Journal of Asian Studies, 2003)
Keywords: dept.his

The historiography of american violence - Leonard, Ira M; Leonard, Christopher C (Homicide Studies, 2003)
Historians have generally agreed that the United States has always been an extremely violent nation; however, since the 1950s they have been myopic in their treatment of violence in America and have not provided the American people with essential information about their society and culture. Those historians who focused on violence in America, until the 1990s, have focused on only one form of violence—collective social violence. Largely overlooked, and equally significant, are interpersonal violence (including criminal and domestic violence) and the effect of war. This deficiency helps explain why Americans seem genuinely at a loss to understand the nature, character, and frequency of violence in America's past and present, especially when a high-profile violent incident occurs. This article surveys the historiography of violence in America through the 1990s and examines the contributions of historians and legal scholars who have focused on interpersonal and criminal violence. © 2003, SAGE Publications. All rights reserved.
Keywords: dept.his; historiography; lynching; riots; vigilantism